110k views
4 votes
If f(x) = 3x - 9 and g(x) = x?, what is (gºf)(5)?

2 Answers

1 vote

Answer:

6

Explanation:

Substitute x = 5 into f(x) then substitute the value obtained into g(x)

f(5) = (3 × 5) - 9 = 15 - 9 = 6, then

g(6) = 6

Hence (g ○ f)(5) = 6

User Dan Lugg
by
5.6k points
2 votes

We have been given the following functions:

f(x) = 3x - 9

g(x) = x

(G*f) means to multiply the function of g and f together:

x(3x - 9)

3x^2 - 9x

Now multiply the product of the solution above by 5:

5(3x^2 - 9x)

15x^2 - 45x

So, (g*f)(5) = 15x^2 - 45x

User Chaggy
by
6.3k points